2021
DOI: 10.3390/brainsci11010107
|View full text |Cite
|
Sign up to set email alerts
|

Using Fractal Dimension Analysis with the Desikan–Killiany Atlas to Assess the Effects of Normal Aging on Subregional Cortex Alterations in Adulthood

Abstract: Normal aging is associated with functional and structural alterations in the human brain. The effects of normal aging and gender on morphological changes in specific regions of the brain are unknown. The fractal dimension (FD) can be a quantitative measure of cerebral folding. In this study, we used 3D-FD analysis with the Desikan–Killiany (DK) atlas to assess subregional morphological changes in adulthood. A total of 258 participants (112 women and 146 men) aged 30–85 years participated in this study. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…Our findings of more pronounced and widespread effects of ageing in males agree with Jao et al (2021), but are not in agreement with (Podg orski et al, 2021), reporting that cortical ageing is more complex in females. The relation between the cortical complexity decline and the clinical implication of its change is not known yet.…”
Section: Trajectories Of Age-associated Change In Cortical Complexitycontrasting
confidence: 88%
See 1 more Smart Citation
“…Our findings of more pronounced and widespread effects of ageing in males agree with Jao et al (2021), but are not in agreement with (Podg orski et al, 2021), reporting that cortical ageing is more complex in females. The relation between the cortical complexity decline and the clinical implication of its change is not known yet.…”
Section: Trajectories Of Age-associated Change In Cortical Complexitycontrasting
confidence: 88%
“…Using the Destrieux parcellation scheme, Madan and Kensinger ( 2016 ) measured shape‐related characteristics with FD in bilateral structures of each lobe ( n = 581, age ranged 20–86) and reported that age‐related decrease in FD was highest in the frontal lobe followed by the parietal lobe while the temporal lobe was least associated with age‐related difference. Recently, Jao et al ( 2021 ) studied subregional cortical changes using 3D‐FD analysis with Desikan–– (DK) atlas ( n = 258, age ranged 30–85 years) and reported a decrease in cortical complexity of all lobes of both hemispheres with age progression from adulthood to old age. The temporal, parietal, and left limbic lobes exhibited a significant decrease from mid‐life (45–60 years) to old age (>60 years).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, two studies observed that the decrease in FD was faster and more significant in males than in females (Jao et al, 2021; Li et al, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…A negative relationship between age and FD has been reported both at the whole‐brain level (Madan & Kensinger, 2016, 2018; Marzi et al, 2020; McDonough & Madan, 2021) and at the regional level in the left DLPFC (Lu, 2020) and in the posterior wall of the right central sulcus (Li et al, 2011). Jao et al (2021) reported regional differences in FD between young adults (<45 years), middle adults (46–60 years) and old adults (>60 years) and observed a reduction in FD from young to middle age in the bilateral frontal, left temporal and right limbic lobes and a reduction in FD from middle to old age in the bilateral temporal, parietal and left limbic lobes. However, they also observed an increase in FD of the left middle orbitofrontal cortex from young to middle age and of the occipital lobe from middle to old age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation